Peran Orangtua dalam Meningkatkan Minat Belajar Daring Pada Masa Pandemi Covid 19 di Kecamatan Selesai Kabupaten Langkat - Milfa Yetty (Maslahah: Jurnal Pengabdian Masyarakat, 2021)
The Covid-19 pandemic has greatly affected the world of education, thus requiring the transition from face-to-face learning to distance learning. However, it is not easy to change face-to-face learning habits into distance learning. As a result of this, all educational institutions, both in cities and districts, have prepared strategies for the implementation of distance learning, because online learning is considered less effective for students. This is in accordance with the results of the pre-test control group obtained a maximum value of 43 and a minimum value of 14.3. The average value is 30.01 and has a standard deviation of 8.09. While the average value obtained by the experimental group is 31.21 and has a standard deviation of 8.15. The results of the post-test online learning assisted by the role of parents at home obtained a maximum score of 90.6 and a minimum score of 62 with an average value of 77.88 and a standard deviation of 8.97. Meanwhile, independent learning without parental assistance obtained a maximum score of 81 and a minimum score of 52.4 with an average score of 66.78 and a standard deviation of 8.68. The value of students with online learning assisted by the role of parents at home is superior to independent learning without parental assistance.